2014
DOI: 10.1152/ajpgi.00305.2013
|View full text |Cite
|
Sign up to set email alerts
|

Marginally excessive iron loading transiently blocks mucosal iron uptake in iron-deficient rats

Abstract: Regular “mucosal block” is characterized by decreased uptake of a normal iron load 3–72 h after the administration of excess iron (generally 10 mg) to iron-deficient animals. We found that short-acting mucosal block could be induced by much lower iron concentration and much shorter induction time than previously reported, without affecting levels of gene expression. A rapid endocytic mechanism was reported to decrease intestinal iron absorption after a high iron load, but the activating iron load and the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…showed a decreased incidence of diarrhea in infants who consumed milk with higher ratios of α(1-2) linked Fuc compared to HMOs with α(1-3/4) linked Fuc26. Previous studies have found 2′-fucosyllactose (2′FL, Fuc(α1-2)Gal(ß1-4)Glc) to be associated with reduced diarrhea incidence caused by Campylobacter jejuni , an infant gastrointestinal pathogen363738. In this study we did not observe any statistically significant associations between reported morbidity and 2′FL.…”
Section: Discussionmentioning
confidence: 99%
“…showed a decreased incidence of diarrhea in infants who consumed milk with higher ratios of α(1-2) linked Fuc compared to HMOs with α(1-3/4) linked Fuc26. Previous studies have found 2′-fucosyllactose (2′FL, Fuc(α1-2)Gal(ß1-4)Glc) to be associated with reduced diarrhea incidence caused by Campylobacter jejuni , an infant gastrointestinal pathogen363738. In this study we did not observe any statistically significant associations between reported morbidity and 2′FL.…”
Section: Discussionmentioning
confidence: 99%
“…Iron transported into the mucosal cells through the apical membrane, but which is not transported to the portal blood, is stored by intracellular ferritin. Ferritin expression in the small intestinal mucosa is controlled by iron nutritional status, and has been shown to be very low in iron-deficient rats 27) . Iron stored in ferritin is lost when mucosal cells exfoliate.…”
Section: Regulation Of Iron Absorption In the Small Intestinementioning
confidence: 99%
“…2) The level of intracellular iron is regulated by iron transporters and iron-binding proteins under normal physiological conditions. 3) Iron deficiency is a worldwide nutritional problem in more than two billion people, mainly women and children. 4) In particular, the iron status of an individual may play an important role in cardiovascular health, not only via excess iron but also via iron deficiency, both of which can lead to significant problems.…”
mentioning
confidence: 99%